External and internal fixation for comminuted intra-articular fractures of distal radius - Pradhan, RL; Lakhey, S; Pandey, BK; Manandhar, RR; Rijal, KP; Sharma, S (Kathmandu University Medical Journal, 2010)
Background: Distal radius fractures are a common injury and without proper treatment leads to high functional impairment and frequent complications. Objective: The aim of this study was to see the functional outcome in patients with comminuted distal radius fractures treated with combined external fixation and open reduction with volar plating. Materials and methods: All comminuted distal radius fractures classified as type C in AO/OTA classification were enrolled for the study from 2005 till 2008. The clinical scoring chart modified by Cooney was used to evaluate the functional outcome. Results: There were twenty-two patients with the average age of 42.18 years (range 19-60) with 15 male and 7 females. The follow-up period was from 14 to 46 months. Accordingly, there were 11 (50%) excellent, 7 (31%) good, 2 (9%) fair and 2 (9%) poor results. There were very few complications in our series. In three patients additional K-wire supplementation was necessary along with external and open internal fixation. Conclusions: Comminuted intra-articular fractures of distal radius should be treated by open reduction and combined internal and external fixation to achieve a high rate of patient satisfaction and satisfactory functional outcome. Key words: distal radius fractures; volar plating; external fixation DOI: 10.3126/kumj.v7i4.2756 Kathmandu University Medical Journal (2009) Vol.7, No.4 Issue 28, 369-373